Metal- and Solvent-Free Synthesis of m-Terphenyls by an Iodine-Catalyzed Tandem Formal [3+3]-Cycloaddition/Oxidation - Pavithra, Thangavel; Karthiyayini, Gnanaoli; Nagarajan, Subbiah; Sridharan, Vellaisamy; Maheswari, C. Uma (Synlett, 2022)
A tandem formal [3+3]-cycloaddition/oxidation between chalcones and β-enamine esters, employing iodine as a catalyst, was developed for the construction of various substituted m-terphenyls. A wide range of chalcones and β-enamine esters were tested under metal- and solvent-free conditions for the synthesis of substituted m-terphenyls in good to excellent yields in the presence of sulfur as an oxidant. This reaction proceeds with the formation of four new bonds and one new ring, with a high atom economy.
Keywords: terphenyls; chalcones; enamine esters; cycloaddition; iodine catalysis; oxidation